2008
DOI: 10.1093/nar/gkn918
|View full text |Cite
|
Sign up to set email alerts
|

Structure–function analysis of the ribozymes of chrysanthemum chlorotic mottle viroid: a loop–loop interaction motif conserved in most natural hammerheads

Abstract: Loop–loop tertiary interactions play a key role in the folding and catalytic activity of natural hammerhead ribozymes. Using a combination of NMR spectroscopy, site-directed mutagenesis and kinetic and infectivity analyses, we have examined the structure and function of loops 1 and 2 of the (+) and (–) hammerheads of chrysanthemum chlorotic mottle viroid RNA. In both hammerheads, loop 1 is a heptanucleotide hairpin loop containing an exposed U at its 5′ side and an extrahelical U at its 3′-side critical for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 36 publications
2
56
0
2
Order By: Relevance
“…More precisely, tertiary interactions between HHR helixes (de la Peña et al 2003;Khvorova et al 2003) show significant conservation in stem size and loop composition (Supplemental Fig. S1; Chi et al 2008;Dufour et al 2009;de la Peña et al 2009). Thus, natural HHR motifs were split into two major helical motifs (seeds), each one composed of either the SC site/Helix I/ U box (I-type seeds) or the U box/Helix II/P box (II-type seeds).…”
Section: Bioinformatic Search Of Hhrsmentioning
confidence: 99%
“…More precisely, tertiary interactions between HHR helixes (de la Peña et al 2003;Khvorova et al 2003) show significant conservation in stem size and loop composition (Supplemental Fig. S1; Chi et al 2008;Dufour et al 2009;de la Peña et al 2009). Thus, natural HHR motifs were split into two major helical motifs (seeds), each one composed of either the SC site/Helix I/ U box (I-type seeds) or the U box/Helix II/P box (II-type seeds).…”
Section: Bioinformatic Search Of Hhrsmentioning
confidence: 99%
“…4A; Dufour et al 2009). Despite these differences, a conserved tertiary interaction motif embedded within the loop-loop complexes has been detected in at least four different hammerheads ( Fig.…”
Section: Hammerhead Ribozymesmentioning
confidence: 98%
“…Despite these differences, a conserved tertiary interaction motif embedded within the loop-loop complexes has been detected in at least four different hammerheads ( Fig. 4; Dufour et al 2009). The 59 U of L2 and the 39 A of L3 form a reverse Hoogsteen pair across the major groove in the X-ray structures of the Schistosoma mansoni (Martick and Scott 2006) and tobacco ring spot virus satellite RNA (Chi et al 2008) (sTRSV) hammerheads, a base pair also supported by site-directed mutagenesis experiments in the hammerheads of the (+) and (À) polarity RNAs Total number of hydrogen bonds contained in the interaction.…”
Section: Hammerhead Ribozymesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have indicated a great variation of tertiary interacting sequences in individual HHRz motifs (Przybilski and Hammann 2007a;Shepotinovskaya and Uhlenbeck 2008), although recurrent signatures were also observed (Dufour et al 2009). The variability of tertiary interacting motifs became even further apparent in several recent database searches for novel HHRz motifs carried out in this and other laboratories Rojas et al 2000;Gräf et al 2005;Przybilski et al 2005;Martick et al 2008;De la Peña and Garcia-Robles 2010;Jimenez et al 2011;Perreault et al 2011;Seehafer et al 2011).…”
Section: Introductionmentioning
confidence: 99%